Penyelesaian Sengketa Uang Kompensasi atas Tanah Ulayat Nagari melalui Lembaga Adat di Nagari Talu Kabupaten Pasaman Barat - Novi Alvionita; Kurnia Warman; Zefrizal Nurdin (UNES Law Review, 2023)
Currently, in the province of West Sumatra, disputes over customary land often occur, including in Nagari Talu, West Pasaman Regency. The background to this dispute was compensation money provided by PLN for the construction of an Extra High Voltage Line (SUTET) on ulayat nagari land which is managed by the community. Meanwhile, the community wants to control all the compensation money. Based on this background, it is necessary to investigate the settlement of ulayat nagari land disputes in Nagari Talu, West Pasaman Regency with the formulation of the problem: What is the process for resolving ulayat nagari land disputes in Nagari Talu, West Pasaman Regency, what obstacles are encountered in resolving ulayat nagari land disputes in Nagari Talu, West Pasaman Regency, how is the control over customary rights of the nagari in Nagari Talu, West Pasaman Regency, after the settlement of the dispute.The research method used through an empirical juridical approach is based on primary legal materials and secondary legal materials as well as field studies through interview observations, as well as data analysis techniques carried out qualitatively. Based on research on the settlement of ulayat nagari land disputes in Nagari Talu West Pasaman Regency, where in this settlement it was first resolved through deliberation by both parties, but in this deliberation no peace was reached, then both parties used a mediator as an intermediary because peace was not achieved, which appointed as a mediator, namely the Nagari Traditional Density Institution (KAN). Kerapatan Adat Nagari (KAN) succeeded in reconciling the two parties and both parties accepted the results of the decision issued by Kerapatan Adat Nagari (KAN). Obstacles faced in resolving ulayat nagari land disputes are caused by several factors, namely internal factors originating from the disputing parties and the object in dispute and external factors originating from other parties. Post-dispute settlement control of ulayat nagari land, based on the decision of the Talu Nagari customary meeting, Ninik Mamak who currently controls ulayat nagari land.